Mastering the technique of taking a rebound on opponent's shield by basketball players of initial level of specialization - Bukova, L. M.; Gordienko, I. A.; Krovyakov, V. F.; Mironenko, Y. I. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: to prove the effectiveness of the use of training program aimed at improving the skill execution of tackling the ball at the opponent's shield attack in basketball specialized base preparation phase.